KONSEP PENETAPAN HARGA PASAR DALAM PERSPEKTIF IBNU KHALDUN DAN IBNU TAIMIYAH DAN RELEVANSINYA PADA PERSAINGAN HARGA ONLINE SHOP SHOPEE - Muthiullah; Aziz, Abdul (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Pricing is an important phenomenon that needs to be studied in more depth. Prices always change from time to time depending on what is influencing them at that time. Changes in demand and supply are things that greatly influence the increase or decrease in prices. Prices in an Islamic economy are influenced by the market conditions within it in the sense that they depend on the level of demand and supply. Ibnu Taymiyah expressed his view that if prices flow naturally according to market conditions, fair prices will emerge so that the government will not allow him to interfere in their regulation.